2013
DOI: 10.5296/ajfa.v5i1.2787
|View full text |Cite
|
Sign up to set email alerts
|

The Value Relevance of Audit report, Auditor Type and Auditor Tenure: Evidence from Iran

Abstract: The aim of this paper is to investigate the value relevance of the audit report, auditor type and auditor tenure in the Iranian context. This study evaluates the effects of various independent variables on the value relevance using a multiple regression analysis approach for 156 companies listed on the Tehran Stock Exchange (TSE) over a 10 year period. The results indicate that audit report has not the value relevance. Hence, unqualified audit report and other audit report are not different in capital market. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 25 publications
0
6
0
4
Order By: Relevance
“…Empiricamente, o relatório de auditoria terá valor informacional relevante se for verificada uma associação com o preço das ações e se essa relação ocasionar mais exatidão na previsão de valores de mercado (Banimahd et al 2013;Barth, 2006).…”
Section: A Opinião Do Auditor Independente E O Mercado De Capitaisunclassified
See 2 more Smart Citations
“…Empiricamente, o relatório de auditoria terá valor informacional relevante se for verificada uma associação com o preço das ações e se essa relação ocasionar mais exatidão na previsão de valores de mercado (Banimahd et al 2013;Barth, 2006).…”
Section: A Opinião Do Auditor Independente E O Mercado De Capitaisunclassified
“…É esperada uma relação positiva com o retorno das ações, pois se espera que as empresas tenham sido auditadas por empresas com maior expertise (Pornupatham, 2015;Robu & Robu, 2015;Banimahd et al, 2013;Arruda et al, 2012); Risco = variável representativa de dependência financeira, sendo a relação entre passivo total e ativo total. Reflete a presença de capital de terceiros, de longo prazo, na estrutura de capital da firma, esperando-se uma relação negativa com o retorno (Pornupatham, 2015;Batista, Pereira, Silva & Imoniana, 2010); ROA = representativa de desempenho, sendo a relação entre o lucro operacional e a diferença entre ativo total e lucro líquido.…”
Section: Metodologiaunclassified
See 1 more Smart Citation
“…It is necessary to observe more reports over time to understand how long the same audit firm is working for the same client. Banimahd et al (2013) found that when the tenure of auditors is long, it has a negative impact on the value relevance of accounting amounts. Assuming auditor tenure as a proxy of the independence of the auditor, the higher the tenure is, the more probable it is that opportunistic behaviours due to familiarity between the audit company and the audited company could make accounting amounts less reliable and relevant for investors' decisions.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…There are also scholars who found no evidence about the relation between the auditor opinion and the value relevance of accounting amounts. Analysing 156 companies listed on the Tehran Stock Exchange (TSE) over a period of 10 years, Banimahd et al (2013) found that unqualified audit reports and other audit reports do not differ in the capital market.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%